Digital Literacy Learning Strategies in School Education: Challenges and Opportunities of the Industrial Revolution 5.0 - Ignatius Joko Dewanto; Zohra Yasin; Nenden Sri Rahayu; Sudirman Sudirman (PT. Anagata Sembagi Education, 2025)
The era of Industrial Revolution 5.0 demands a significant transformation in the education system, especially in the development of digital literacy. Digital literacy includes not only the technical ability to use technology, but also a critical understanding of the social, ethical and security impacts in the digital world. This study aims to explore digital literacy learning strategies in the school environment, identify the challenges faced, as well as the opportunities that arise in facing the demands of the Industrial Revolution 5.0. The research method used is a literature study and case analysis of various best practices in schools. The results showed that the integration of a digital literacy-based curriculum, teacher training and collaboration with external parties such as industry and communities are key strategies. Key challenges include gaps in technology access, lack of teacher readiness and the dynamics of rapid technological change. However, the Industrial Revolution 5.0 also opens up opportunities to create learning that is more personalized, collaborative and oriented towards developing 21st century skills. In conclusion, schools need to adopt a holistic and sustainable approach to integrating digital literacy to prepare students for an increasingly digitized future.